Evidence of indirect gap in monolayer WSe2. Issue 1 (December 2017) - Hsu, Wei-Ting; Lu, Li-Syuan; Wang, Dean; Huang, Jing-Kai; Li, Ming-Yang; Chang, Tay-Rong; Chou, Yi-Chia; Juang, Zhen-Yu; Jeng, Horng-Tay; Li, Lain-Jong; Chang, Wen-Hao
Abstract Monolayer transition metal dichalcogenides, such as MoS2 and WSe2, have been known as direct gap semiconductors and emerged as new optically active materials for novel device applications. Here we reexamine their direct gap properties by investigating the strain effects on the photoluminescence of monolayer MoS2 and WSe2 . Instead of applying stress, we investigate the strain effects by imaging the direct exciton populations in monolayer WSe2 –MoS2 and MoSe2 –WSe2 lateral heterojunctions with inherent strain inhomogeneity. We find that unstrained monolayer WSe2 is actually an indirect gap material, as manifested in the observed photoluminescence intensity–energy correlation, from which the difference between the direct and indirect optical gaps can be extracted by analyzing the exciton thermal populations. Our findings combined with the estimated exciton binding energy further indicate that monolayer WSe2 exhibits an indirect quasiparticle gap, which has to be reconsidered in further studies for its fundamental properties and device applications. Monolayer transition metal dichalcogenides have so far been thought to be direct bandgap semiconductors. Here, the authors revisit this assumption and find that unstrained monolayer WSe2 is an indirect-gap material, as evidenced by the observed photoluminescence intensity-energy correlation.